Pengaruh Pendekatan Realistic Mathematics Education (RME) Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII SMP Negeri 2 Kabun - Nur Syafitri, Citra; Astuti; Hidayat, Adityawarman; Bahasa Indonesia; Bahasa Indonesia, Bahasa Indonesia (Jurnal PEKA (Pendidikan Matematika), 2025)
This research was motivated by the low mathematical problem-solving abilities of class VIII students at SMP Negeri 2 Kabun. One solution to overcome this problem is to use Realistic Mathematics Education (RME) approach.This research aims to determine whether or not there is an influence between student who use the RME approach and student who use a conventional approach on problem solving abilities. This research is a quasi-experimental study using a posttest only design with nonequivalent group. The research subjects consisted of class VIII A, totaling 27 students and VIII B, totaling 27 students. The sampling technique used is random sampling. The data collection techniques used were observation sheets and mathematical problem-solving ability test questions. The results of this research can be concluded that the RME approach can influence the mathematical problem-solving abilities of class VIII students at SMPN 2 Kabun. This can be proven through the t test from the two groups, it was found that  2,00 with a significance level of α5%. Because the value of (6,94  2,00) then is rejected and  is accepted